2021
DOI: 10.1111/apa.16083
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal sepsis prediction through clinical decision support algorithms: A systematic review

Abstract: Aim: To systematically summarise the current evidence of employing clinical decision support algorithms (CDSAs) using non-invasive parameters for sepsis prediction in neonates. Methods: A comprehensive search in PubMed, CENTRAL and EMBASE was conducted. Screening, data extraction and risk of bias were performed by two authors. The certainty of the evidence was assessed using GRADE. PROSPERO ID: CRD42020205143. Results: After abstract and full-text screening, 36 studies comprising 18,096 infants were included. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 56 publications
(390 reference statements)
0
42
0
Order By: Relevance
“…Research suggests that biomarkers (such as C-reactive protein and certain toll-like receptors 28 ), and new metagenomic sequencing to rapidly identify pathogens from normally sterile fluids, could help to diagnose infection. New neonatal sepsis predictive algorithm tools have also been developed, 29 , 30 , 31 but it is unlikely that physicians would have this information or technology available in low-resource public health settings.…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that biomarkers (such as C-reactive protein and certain toll-like receptors 28 ), and new metagenomic sequencing to rapidly identify pathogens from normally sterile fluids, could help to diagnose infection. New neonatal sepsis predictive algorithm tools have also been developed, 29 , 30 , 31 but it is unlikely that physicians would have this information or technology available in low-resource public health settings.…”
Section: Discussionmentioning
confidence: 99%
“…a) Logistic regression (LR): Logistic regression (LR) is a model that is often used for neonatal sepsis prediction algorithms [20]. LR models the relationship between x and it's label using a sigmoid function and a weighted sum of the components in x.…”
Section: Algorithmsmentioning
confidence: 99%
“…The interpretability of prediction algorithms is often required by clinicians to motivate their actions based upon a classification result [19]. This often leads to the choice of linear prediction algorithms to build feature based classifiers [20]. Linear prediction algorithms can yield an importance score for each input feature which directly explains the classification result to clinicians [14], [15].…”
Section: Introductionmentioning
confidence: 99%
“…Persad et al evaluated the use of clinical decision support algorithms that assess non‐invasive parameters to predict neonatal sepsis 8 . Their systematic review indicated that heart rate‐based parameters were reliable components of clinical decision support algorithms that predicted sepsis, particularly when they were combined with other vital signs and demographics.…”
Section: Review Highlights the Need For More Research On Algorithms T...mentioning
confidence: 99%